2013
DOI: 10.4239/wjd.v4.i4.130
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes and celiac disease: The effects of gluten free diet on metabolic control

Abstract: Type 1 diabetes mellitus is associated with celiac disease, with a prevalence that varies between 0.6% and 16.4%, according to different studies. After a diagnosis of celiac disease is confirmed by small bowel biopsy, patients are advised to commence a gluten-free diet (GFD). This dietary restriction may be particularly difficult for the child with diabetes, but in Europe (and in Italy) many food stores have targeted this section of the market with better labeling of products and more availability of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 40 publications
1
67
0
3
Order By: Relevance
“…We have not observed any difference in the diabetes associated Ab profile for children with optimal or poor glycemic control. This is in agreement with previous studies that found no correlation between single and/or combined diabetes Ab positivity and diabetes control where some pancreatic function was preserved [39,40,46]. However, interestingly it was proved recently, that autoimmune thyroiditis accompanying T1DM is associated with worse glycemic control and lipid profile [47].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We have not observed any difference in the diabetes associated Ab profile for children with optimal or poor glycemic control. This is in agreement with previous studies that found no correlation between single and/or combined diabetes Ab positivity and diabetes control where some pancreatic function was preserved [39,40,46]. However, interestingly it was proved recently, that autoimmune thyroiditis accompanying T1DM is associated with worse glycemic control and lipid profile [47].…”
Section: Discussionsupporting
confidence: 81%
“…The association of T1DM and AITD is highly dependent on age, sex and ethnicity [36]. Approximately 10% of T1DM patients are affected by CD with prevalence ranging from 0.6% to 16.4% reported in different studies [10,[37][38][39] and that is significantly higher than in non-diabetic children (1%-2% of the population). CD and T1DM may develop in parallel however usually T1DM precedes the onset of CD [40].…”
Section: Discussionmentioning
confidence: 99%
“…Pertaining to metabolic control, many gluten-free foods used in the management of CD have a high glycemic index [9]. This could potentially influence glycemic control and the development of acute metabolic complications (diabetic ketoacidosis and hypoglycemia).…”
mentioning
confidence: 99%
“…About 4-9 % of patients with T1D develop CD [323,324]. Children with T1D undergo screening for CD since less than 10% of patients with T1D who develop CD show gastrointestinal symptoms, thus most of the children are either asymptomatic or only mildly symptomatic [325].…”
Section: Associated Diseasesmentioning
confidence: 99%